Antiviral efficacy of silicon nitride against SARS-CoV-2 and MERS-CoV: implications for PPE innovation - Heath, Brittany N.; Woodson, Caitlin M.; McMinn, Chelsey; Bock, Ryan M.; Kehn-Hall, Kylene (Frontiers in Microbiology, 2025)
Medical interventions, such as masks, were a cornerstone in mitigating the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since 2019, the scientific community has increasingly focused on exploring avenues for pandemic prevention and preparedness to enhance responses to future viral outbreaks. One such area of interest explores the use of additives, such as silicon nitride (Si₃N₄), in masks to enhance the antiviral properties of personal protective equipment. Si₃N₄ powder has been shown to inactivate SARS-CoV-2 under aqueous conditions, with a similar yet modest reduction in virus when embedded into non-woven fabric. This study aimed to optimize the use of Si₃N₄ as an antiviral agent. We addressed this knowledge gap by comparing the viral inactivation potential of β-Si₃N₄ and α-Si₃N₄ powders against multiple SARS-CoV-2 lineages and Middle Eastern respiratory syndrome coronavirus (MERS-CoV). Additionally, we tested a refined non-woven fabric embedded with α-Si₃N₄ against SARS-CoV-2 (Lineage A). The results presented here suggest that α-Si₃N₄ was the most effective in reducing the infectious virus through viral RNA degradation, as determined by plaque assay and RT-qPCR. The most promising finding was the significant reduction of SARS-CoV-2 after only 10 min of exposure to refined α-Si₃N₄-embedded fabric. Thus, silicon nitride could be an invaluable inorganic additive in personal protective equipment during future viral epidemics and pandemics.